PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR SISTEM KOORDINASI PADA SISWA KELAS XI-A1 SMA NEGERI 1 MANYARAN - WANTI KURNIASIH (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This research is a classroom action research that aims to improve student learning outcomes in the Coordination System material through the application of the Teams Games Tournament learning model. The research subjects were 34 students of class XI-IPA 1 at SMAN 1 Manyaran for the 2021/2022 academic year. The research was carried out in 2 cycles and the collected data were analyzed using comparative descriptive analysis. The results showed that the application of the Teams Games Tournament cooperative learning model could improve the learning outcomes of the Coordination System in class XI-IPA 1 SMAN 1 Manyaran. This increase was shown by the results of the research from cycle 1 to cycle 2, namely 1) the average acquisition of the posttest results of cycle 1 was 74.41 and increased to 82.94 in the second cycle. 2). The number of students who completed in cycle 1 was 25 out of 34 students with an achievement percentage value of 73.53%, while in cycle 2, the number of children who completed increased to 28 out of 34 students with an achievement percentage value of 82.35%. ABSTRAKPenelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan hasil belajar siswa pada materi Sistem Koordinasi melalui penerapan model pembelajaran Teams Games Tournament. Subyek penelitian adalah 34 orang siswa kelas XI-IPA 1 SMAN 1 Manyaran Tahun Pelajaran 2021/2022. Penelitian dilaksanakan dalam 2 siklus dan data yang terkumpul dianalisis dengan menggunakan analisis deskriptif komparatif . Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif Teams Games Tournament dapat meningkatkan hasil belajar Sistem Koordinasi pada siswa kelas XI-IPA 1 SMAN 1 Manyaran. Peningkatan tersebut ditunjukkan oleh hasil penelitian dari siklus 1 ke siklus 2 yaitu 1) perolehan rata-rata hasil posttest siklus 1 sebesar 74,41 dan meningkat menjadi 82,94 di siklus kedua. 2). Jumlah siswa yang tuntas pada siklus 1 adalah 25 dari 34 anak dengan nilai prosentase ketercapaian sebesar 73,53%, sedangkan pada siklus 2, jumlah anak yang tuntas bertambah menjadi 28 dari 34 siswa dengan nilai prosentase ketercapaian sebesar 82,35%.